Pred/iction of cardiovascular events in subjects in the second australian national blood pressure study - Nelson, M.; Ryan, P.; Tonkin, A.; Ramsay, E.; Willson, K.; Wing, L.; Reid, Christopher (American Heart Association, 2010)
Estimating absolute risk rather than measurement of blood pressure alone is considered the best way to identify those who would most likely benefit from medical intervention. Risk calculators used to estimate risk in those without previous cardiovascular disease (CVD) events are based on the Framingham Heart Study, which had no person >74 years of age at baseline. This needs to be addressed, because age is the most important determinant of risk. We estimated the predictive value of 3 risk equations for CVD end points in the Second Australian National Blood Pressure study cohort (mean age: 71.9 years at baseline). Observed and predicted 5-year incidence rates, ? goodness-of-fit tests, and Harrell C statistic and area under the receiver operator characteristic curve were used to assess the ability of the equations to predict CVD outcomes over 5 years. A recalibration analysis was undertaken. Significant (P<0.05) ?2 goodness-of-fit statistics were observed using each of the risk equations for myocardial infarction, coronary heart disease, stroke, or CVD morbidity or mortality across age groups and both sex. All of the overall C statistics or the area under the receiver operator characteristic curve indicated modest discrimination of the algorithms for prediction of the outcomes for coronary heart disease and CVD morbidity and mortality, myocardial infarction, or stroke (Framingham); cardiac death (Pocock); and CVD events (Dubbo). Recalibration analyses showed that it would be inappropriate to apply the risk equations to the Second Australian National Blood Pressure study population. New risk equations for CVD events in the hypertensive aged are needed. © 2010 American Heart Association, Inc.